An improved numerical distance relay based on CCVT transient characteristic matching. (November 2020) - Chen, Yu; Wen, Minghao; Wang, Zhen; Yin, Xianggen; Peng, Jiang; Zhang, Rui
Highlights: An improved distance relay based on CCVT transient characteristic matching is proposed. The virtual digital CCVT is applied to reduce the influence of CCVT on distance relays. A cascade IIR filter is introduced to match the CCVT transient characteristics. Experimental results show that the proposed distance relay has the fast operation speed. Abstract: The transients of the coupling capacitor voltage transformer (CCVT) have an impact on the performance of distance relays and result in the overreach problem. Based on the equal transfer process of transmission lines (ETPTL) theory, the virtual digital CCVT can be applied to reduce the impact of the CCVT transients and improve the operation speed of distance relays. The virtual digital CCVT is required to have the same transient characteristics as the actual CCVT. This paper proposes a simple and universal design method of virtual digital CCVT. Based on the CCVT transient characteristic matching and the ETPTL theory, this paper proposes an improved numerical distance relay algorithm to prevent the overreach problem of distance relays without sacrificing the operation speed of distance relay under the internal fault conditions. An extensive performance evaluation using PSCAD/EMTDC simulation corroborates the effectiveness of the proposed distance relay under different fault conditions. Finally, a prototype device based on the proposed distance relay is developed in laboratory and evaluated through a hardware in loop test using real-time digital simulator (RTDS).